2015
DOI: 10.4037/ajcc2015386
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Ulcer Incidence in Patients Wearing Nasal-Oral Versus Full-Face Noninvasive Ventilation Masks

Abstract: A closed-book, multiple-choice examination following this article tests your under standing of the following objectives:1. Explain the importance of checking for pressure ulcers. 2. Identify areas of high risk for skin breakdown. 3. Enumerate advantages of wearing a full-face mask.To read this article and take the CE test online, visit www.ajcconline.org and click "CE Articles in This Issue. " No CE test fee for AACN members.Background Device-related pressure ulcers from noninvasive ventilation masks alter ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 14 publications
(19 reference statements)
0
63
0
4
Order By: Relevance
“…However, patient discomfort and complications might limit continuous application of NIV [7], further decrease its efficacy, and even increase mortality. Some of these complications and discomfort were related to the mask [79, 38]. In order to improve tolerability for patients, a transparent helmet made from latex-free polyvinyl chloride was developed [13].…”
Section: Discussionmentioning
confidence: 99%
“…However, patient discomfort and complications might limit continuous application of NIV [7], further decrease its efficacy, and even increase mortality. Some of these complications and discomfort were related to the mask [79, 38]. In order to improve tolerability for patients, a transparent helmet made from latex-free polyvinyl chloride was developed [13].…”
Section: Discussionmentioning
confidence: 99%
“…Skin assessment should begin at the areas that directly contact the mask, and those areas should be reassessed at least once per shift 35. However, Bambi et al,33 argued that skin assessment should be performed every 2 to 4 hours because clinical studies showed that pressure ulcers can develop in 4 to 6 hours under a continuous load.…”
Section: Risk Factors For Facial Pressure Ulcers Development and Theimentioning
confidence: 99%
“…The maximum time for continuous NIV is 11 hours. After that time, it is recommended to remove the interface and allow the skin to rest for at least 4 hours 35,40…”
Section: Risk Factors For Facial Pressure Ulcers Development and Theimentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, measures to prevent PU consider the use of suitable masks, with strong evidence for the use of the total face mask model, as well as periodical revision of the skin and the placement of facial patches between the skin and the mask in risky areas 10,[16][17][18] . The protective patches are intended to create a physical barrier between the mask and the skin, in order to theoretically attenuate the pressure exerted on the skin, in an effect that we could call "meniscus effect", given the functional similarity achieved by the cartilaginous (meniscus) joint in the knee 19 .…”
Section: Face Protective Patches Do Not Reduce Facial Pressure Ulcersmentioning
confidence: 99%